Solving complex industrial problems without statistics - Pawlak, Ralph R. (CRC Press, Taylor & Francis Group, 2016)
Introducing a process that involves working through problems and solutions without relying on complicated statistical design or analysis, this book pulls away from data-driven thinking and provides the problem solver with a new way of solving problems.